2021
DOI: 10.3390/app11041611
|View full text |Cite
|
Sign up to set email alerts
|

Case Study of Underground Shield Tunnels in Interchange Piles Foundation Underpinning Construction

Abstract: Technology of shield tunneling has been widely used in modern city subway system building, however, due to the limit of urban construction land resources, it is inevitable for the new building structures conflicted with existing one. Thus, it is essential to taking correct measures to guarantee the safety of existing structure. In this case, a typical case of metro shield tunnel crossing through city overpass bridge piles underpinning construction project is studied by the numerical method and site field monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Many scholars at home and abroad have studied the problem of bridge settlement. Fang [1] studied the impact of the existing bridge on the settlement of all parts of the newly built adjacent bridge piles; Zhou [2] put forward a method to calculate the long-term settlement of pile foundation, considering the creep characteristics of layered soil consolidation at the pile; Zhang [3] analyzed the in uence of pressure water on the settlement of cluster pile foundation by means of indoor three-axial test and nite element numerical simulation; Liu [4] analyzed the causes of the surface and the settlement of the bridge, and believed that the settlement was caused by the collapse of the uncompacted area caused by the in uence of rain; Liu [5]studied the cause of the settlement disease of the double-pillar pier foundation of a new highway bridge, and found that the insu cient bearing capacity and the pile body defects caused the uneven settlement of the pile foundation; Wang [6] adopted the method of nite element analysis to establish the model of high-speed railway bridge and analyzed the settlement of highway and bridge; Zhang [7] uses numerical simulation, and believes that the construction of shield tunneling technology under existing Bridges has little impact on the settlement of existing Bridges.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars at home and abroad have studied the problem of bridge settlement. Fang [1] studied the impact of the existing bridge on the settlement of all parts of the newly built adjacent bridge piles; Zhou [2] put forward a method to calculate the long-term settlement of pile foundation, considering the creep characteristics of layered soil consolidation at the pile; Zhang [3] analyzed the in uence of pressure water on the settlement of cluster pile foundation by means of indoor three-axial test and nite element numerical simulation; Liu [4] analyzed the causes of the surface and the settlement of the bridge, and believed that the settlement was caused by the collapse of the uncompacted area caused by the in uence of rain; Liu [5]studied the cause of the settlement disease of the double-pillar pier foundation of a new highway bridge, and found that the insu cient bearing capacity and the pile body defects caused the uneven settlement of the pile foundation; Wang [6] adopted the method of nite element analysis to establish the model of high-speed railway bridge and analyzed the settlement of highway and bridge; Zhang [7] uses numerical simulation, and believes that the construction of shield tunneling technology under existing Bridges has little impact on the settlement of existing Bridges.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complex construction environment in cities and limitations of alignment planning of the tunnel, tunnels adjacent to the existing piles of buildings appear frequently [1][2][3][4]. In particular cases, tunnels are passing through the existing piles [5][6][7]. e shield tunneling method is widely used in tunnel engineering, for its advantage of safety, e ciency, high mechanization degree, and small disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…e shield tunneling method is widely used in tunnel engineering, for its advantage of safety, e ciency, high mechanization degree, and small disturbance. Compared to the methods of tunnel rerouting and pile underpinning [6,8], cutting the piles directly using the shield cutter is more economical and e cient when shield tunnels pass through the existing reinforced concrete (RC) piles, and it has wide application prospects. During the process of shield cutting piles, parameters con guration of cutter and shield working is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…This will ensure collisions between pedestrians, electric vehicles, bicycles, and cars are avoided at ground traffic intersections. Therefore, how to choose the construction location of an overpass and what type of overpass to build [24] will directly affect the traffic situation of the entire urban road traffic network. If the site selection is correct, it will effectively alleviate the traffic situation in the surrounding area.…”
Section: Introductionmentioning
confidence: 99%